Judicial Institution and Judicial Power: How Judicial Authority Existence in Administering Judicial Power in the Islamic View - Sudirman L; Anwar, Wirani Aisiyah; Sunuwati, Sunuwati; Wahyu, A. Rio Makkulau (DIKTUM: Jurnal Syariah dan Hukum, 2022)
The judiciary is very important thing to be paid attention, due to its effects on the integrity of the nation as well as state, even in the pre-Islam era up to current days. This study aims to expose the existence of the judicial institution`s authority in administering a judicial power. This research applied library method. The data collected form literature, and the analysis technique used the descriptive analysis based on the evidence of judicial institutions. The court is authority institutions which conduct a justice, trough examining and deciding cases of legal disputes or violations of laws. Wilayatul Hisbah whose main authority is to settle minor criminal acts which are do not require a judicial process in their settlement. In supporting this authority, there is such fatwa council, tahkim or arbitration institution that was held as an institution for implementing judicial power in Islam